Knowledge on sexually transmitted infections among HIV-pre-exposure prophylaxis users in Nairobi city county, Kenya - Kibala, Emmanuel K.; Kimani, Harun M.; Orinda, George O.; Marwa, Tom M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Sexually transmitted infections remain a significant public health problem mainly in low-income countries. Despite the high efficacy of HIV-PrEP, an upsurge of STIs is recorded globally after HIV-PrEP introduction due to sexual behaviour change among the users. Nairobi has the highest rate of HIV-PrEP uptake and large number of HIV-PrEP users visit health facilities to get treatment for STIs. This study aimed to assess knowledge on STIs among HIV-PrEP users in Nairobi, Kenya. Methods: Analytical cross-sectional research design was employed. Simple random sampling technique was adopted to obtain a sample size of 357 respondents seeking HIV-PrEP service in five health facilities in Nairobi, from July to November 2022. The study used primary data which was collected using structured questionnaire and secondary data (laboratory results). Results: Most of the respondent were knowledgeable about STIs occurrence. 56.7% of the respondents knew that STIs could be transmitted through sex without using condom, 43.3% knew that sex with sex workers could make one get STIs, 58.7% of the respondents were aware that STIs could be transmitted through sexual contact with multiple partners. A statistically significant association was found between STI related level of knowledge and STIs prevalence among HIV-PrEP users in Nairobi. Conclusions: The knowledge about STIs among HIV-PrEP users in Nairobi does not translate into safe sexual behaviour against STIs. The study recommends that the facility management and service providers should encourage HIV-PrEP users to undertake routine STIs screening tests and treatment as well as frequent safe sexual behaviour awareness creation education.